Pelaporan SPT Tahunan Wajib Pajak Orang Pribadi Menggunakan Electronic Filing - Setiadi, Agnya Salsabila; Sari, Ervina Indri; Adnyana, I Gede Sudi (Jurnal Aplikasi Bisnis Kesatuan, 2024)
Tax Reporting, E-Filing and Personal Taxpayers           _______257       Submitted FEBRUARY 2024   Accepted JULY 2024                                             JABKES   Jurnal Aplikasi Bisnis Kesatuan Vol. 4 No. 2, 2024 page. 257-262 IBI Kesatuan ISSN 2807 – 6036 DOI: 10.37641/jabkes.v4i2.2010       KPP Pratama Ciawi is a tax office that operates in general and aims tcollect revenue through tax reporting activities. Annual SPT reporting is an obligation that must be carried out by individual taxpayers. In the digital era, electronic filing, or E-filing, has become an alternative introduced by the Directorate General of Taxes to simplify the online tax reporting process. The purpose of this research is to review the procedure for reporting the annual SPT of individual taxpayers using E-filing. The results of this study indicate that E-filing provides many advantages for individual taxpayers. The reporting process can be carried out flexibly and efficiently without the need to queue at the tax office. In addition, E-filing allows taxpayers to fill out and send annual tax returns in real time via electronic devices such as computers, laptops, or smartphones.   Keywords: Tax Reporting, E-filing